C♯ puzzlers - Wagner, Bill (LiveLessons., 2011)
"How well do you know C♯? Put your knowledge to the test in Bill Wagner's C♯ Puzzlers video LiveLesson! Bill Wagner's C♯ Puzzlers exposes common misconceptions that developers have about the C♯ language. Misconceptions occur when developers are unclear about how language features interact. On other occasions, a lack of understanding about how a single features works, can stump and frustrate the most experienced developer. Using the "Puzzler" format, Bill demonstrates these misconceptions using small code samples; he then explores different ways for you to modify the code until its behavior is correct. This collection of Puzzlers is divided into seven sections. Each section delves into the rules that govern aspects of the C♯ language that developers find most confusing: I. Generics II. Method Resolution III. Named and Optional Parameters IV. LINQ V. Value and Reference Semantics VI. Dynamic Programming in C♯"--Resource description page.